Intraoperative radiotherapy in elderly patients with breast cancer: long-term follow-up results of the prospective phase II trial TARGIT-E - Sperk, Elena; Lemanski, Claire; Neumaier, Christian; Lauer, Juliane; Siefert, Victor; Völker, Ragna; Lindner, Christoph; Niehoff, Peter; Tallet, Agnes Richard; Racadot, Séverine; Petit, Adeline; Pazos, Montserrat; et al. (BMC cancer, 2025)
Whole-breast radiotherapy (WBRT) after breast-conserving surgery (BCS) in older patients can be challenging due to the increased presence of comorbidities, comedication, the presence of a pacemaker or difficulties in traveling to treatment every day. Challenging times, such as the pandemic, can also lead to RT not being performed despite the indication. Very short treatment regimens are therefor of special interest in this population reducing overall treatment time and radiation exposure. TARGIT-E is a phase II trial investigating intraoperative radiotherapy (IORT) during BCS in elderly patients. We report long-term follow-up results of TARGIT-E.